N.V. Nederlandsche gist- & spiritusfabriek Delft : de ontwikkeling der onderneming in zestig jaren 1870-1930. (Delft : Van Markens, 1930)
Bibliotheek E. Anseele
Nederlands
Monografie
Keywords: bedrijfsleven